Effect of Combination of Rosmarinic Acid with Valsartan and Irbesartan on NO and ADMA Levels in Diabetic Nephropathy Model Rats - Tidel, Caesar; Samsu, Nur; Rifai, Achmad (Universitas Brawijaya, 2025)
Background: Diabetic nephropathy (DN) is a complication that often occurs in diabetes mellitus, in which the kidneys are damaged. Nitric oxide (NO) and Asymmetric Dimethylarginine (ADMA) are mediators that play a role in the pathophysiology of DN. Rosmarinic acid (AR) is an antioxidant compound that has the potential to be an alternative treatment for diabetic nephropathy. Valsartan and Irbesartan are antihypertensive drugs that have a nephroprotective effect. However, no studies have studied the concomitant use of AR with these two antihypertensive drugs. Aim: To identify the effect of the combination of AR and Valsartan and Irbesartan on NO and ADMA levels in DN rat models.. Methods: True experimental laboratory design and a randomized posttest only controlled group design method. The rats were divided into four groups, namely the negative control group, positive control (diabetic rats without therapy), group 3 (AR) 75 mg/kgBW/day with Irbesartab 1.5 mg/kg BW/day) and group 4 (AR) 75 mg/kgBW /day with Valsartan 1 mg/kg/day). Data were analyzed using One-way ANOVA with a significance level of p<0.05. Results: Administration of Valsartan (79.42±13.95 µmol/L) and Irbesartan (84.62±18.59 µmol/L) significantly increased NO levels compared to the positive control (61.49±8.03 µmol/L) (p< 0.05). Administration of Valsartan (57.87 ± 9.29 ng/mL) and Irbesartan (53.77 ± 9.42 ng/mL) did not decrease NO levels compared to control (50.46 ± 8.52 ng/mL) (p> 0.05 ). Conclusion: Administration of valsartan and irbesartan increased NO levels in DN rats exposed to rosmarinic acid. However, administration of valsartan and irbesartan did not affect ADMA levels in DN rats exposed to rosmarinic acid.